Comparison of tibial impact accelerations: video vs accelerometer - Petushek, E. J.; Richter, C.; Donovan, D.; Ebben, W. P.; Jensen, R. L. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
This study compared tibial axial accelerations measured by video analysis and accelerometry. Twenty-two recreationally active adults performed three countermovement jumps. The landing tibial axial accelerations were assessed with video and an accelerometer. High reliability was demonstrated for the root mean square error between the assessment methods (ICCave = 0.872). Repeated measures ANOVA results revealed no instrumentation differences in the magnitude of the two acceleration peaks (toe and heel contact) and no difference between trials. However, first and second peaks occurred 9.6 and 4.0 ms earlier, respectively, when assessed by video. Accelerometry is a valid and reliable alternative to video analysis for the assessment of tibial impact accelerations if temporal characteristics are not of interest.